2022
DOI: 10.1007/s10278-022-00732-6
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-based Non-rigid Image Registration for High-dose Rate Brachytherapy in Inter-fraction Cervical Cancer

Abstract: In this study, an inter-fraction organ deformation simulation framework for the locally advanced cervical cancer (LACC), which considers the anatomical flexibility, rigidity, and motion within an image deformation, was proposed. Data included 57 CT scans (7202 2D slices) of patients with LACC randomly divided into the train (n = 42) and test (n = 15) datasets. In addition to CT images and the corresponding RT structure (bladder, cervix, and rectum), the bone was segmented, and the coaches were eliminated. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…This registration pipeline starts with a classification network for coarse orientation estimation, followed by a segmentation network for predicting ground-truth planes in 3D volumes, enabling fully automated slice-to-volume registration in one shot. In [464], a method for the deformation simulation of inter-fraction in high-dose rate brachytherapy was proposed, which is applied to the deformable image registration (DIR) algorithm based on deep learning, which can directly realize the inter-fraction image alignment of HDR sessions for inter-fraction high dose rate brachytherapy in cervical cancer.…”
Section: Image Registrationmentioning
confidence: 99%
“…This registration pipeline starts with a classification network for coarse orientation estimation, followed by a segmentation network for predicting ground-truth planes in 3D volumes, enabling fully automated slice-to-volume registration in one shot. In [464], a method for the deformation simulation of inter-fraction in high-dose rate brachytherapy was proposed, which is applied to the deformable image registration (DIR) algorithm based on deep learning, which can directly realize the inter-fraction image alignment of HDR sessions for inter-fraction high dose rate brachytherapy in cervical cancer.…”
Section: Image Registrationmentioning
confidence: 99%
“…The source image is then warped by resampling from the mapped locations. Some of the potential applications of DIR in medical imaging are dose accumulation in radiation treatment, contour propagation, tumor growth tracking, and creating a digital atlas (Mohammadi et al, 2019;Rigaud et al, 2019;Zhao et al, 2022;Salehi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of deep learning in the past few years, multiple deep learning based DIR approaches have been proposed (Balakrishnan et al, 2019;de Vos et al, 2017;Li and Fan, 2018;Li et al, 2022;Salehi et al, 2022;Rigaud et al, 2019), which provide the possibility to predict the DVF for an entire volumetric scan within seconds. However, to the best of our knowledge, there is no work done in the direction of MO DIR using deep learning.…”
Section: Introductionmentioning
confidence: 99%
“…One approach to robustly handle large deformations is to use regularization constraints such as rigidity penalty 27 and geometry matching constraints used for successfully aligning images exhibiting large anatomic deformations such as upper GI organs 27 and female reproductive organs such as the uterus and cervix 28 . A recent DLIR method by Han et al 29 .…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16]26 One approach to robustly handle large deformations is to use regularization constraints such as rigidity penalty 27 and geometry matching constraints used for successfully aligning images exhibiting large anatomic deformations such as upper GI organs 27 and female reproductive organs such as the uterus and cervix. 28 A recent DLIR method by Han et al 29 have also shown that using geometry constraints can benefit handling large anatomic differences inherent in organs like the small and large bowel when aligning CBCT images with CT images. Our proposed method also uses geometry matching losses during training to better regularize the registration and segmentation sub-networks with a key difference that such losses are used also as deep supervision losses to optimize the incremental deformations computed by the network.…”
Section: Introductionmentioning
confidence: 99%